ESPACIO Y REPRESENTACIÓN EN LA PINTURA DE MANUEL QUEJIDO Y GUILLERMO PÉREZ VILLALTA - Carrillo Castillo, Jesús María (Imafronte, 1991)
This paper alludes to the wide discussion on the definition of the space, since de first eavantgardes. till the most recent ones, and proposes certain conclusions on tlie subject. The pictorial surjaces, the new spaces, are considered through the work of Manuel Quejido and Guillermo Pérez Villalra. They were chosen because of their belonging to the sume pictorial generation and their artistic relationship to the gallery Buades, though we cannot find a unity of style between them both, as they are separated by a series of differences.